A coupled elastoplastic damage model for brittle rocks - Zheng Li; Yundong Shou; Deping Guo; Filippo Berto (Fracture and Structural Integrity)
Brittle rock contains an important plastic deformation, which causes microcracks when coupled with stress-induced damage. A new coupled elastoplastic damage model is established in order to discuss the damage behaviors found in brittle rock, based on theoretical analysis and experiments. Micromechanic considerations determine the effective elastic properties of anisotropic damaged geomaterials. An energy-based damage criterion is used to deduce the damage initiation and the damage evolution law of the brittle rocks. Moreover, the non-linear unified strength criterion is modified. It takes anisotropic damage and the effects of intermediate principal stress into account, in order to determine both the yield and plastic potential functions. The non-associated plastic flow rule is utilized. The consistency condition of plastic and damage is applied in the coupled process. The damage evolution rule and the coupled plastic damage of brittle rock are conceived within the framework of irreversible thermodynamics. By comparing the simulations and the experimental data from limestone that was subjected to various loading paths, a strong connection between the numerical simulations and experimental data is therefore obtained. The numerical results show that the new model is able to describe the main features of the mechanical properties observed in brittle rock.